Financial Norms for Collection Development in Libararies - Gopinath, M. A. (Journal of Information and Knowledge, 1983)
Financial norms for collection development for libraries is based on variety of factors. The principal factor is the usage of collection. The expression of this in modern budget procedure for libraries is indicated. The comparatative profile of financial norms for university and college libraries, special libraries and public libraries in India, United Kingdom and the United States of America illustrates this.